Wald und Wasserhaushalt: Die Bedeutung neuer Versuche im Harz - Keller, Reiner (ERDKUNDE, 1953)
Only six experiments in the whole world can be considered as positive contributions to the discussion of the old problem of the influence of forest cover on water regime. But since these experiments have been undertaken in different climatic zones and have used differing methods, no generalisations should be made. In this paper first results of new experiments carried out in forested and deforested areas in the Harz mountains are reported; they provide, among other things, data regarding evaporation, run-off and precipitation, and further, on the transport of suspended matter and pebbles. One result emerging is that forest cover indeed alters the run-off curve but does not raise the level of the low water mark on it.